Appalachian children's literature an annotated bibliography - Herrin, Roberta T. (Contributions to southern Appalachian studies, 2010)
"This bibliography includes books written about or set in Appalachia from the 18th century to the present. Titles represent the entire region as defined by the Appalachian Regional Commission. The bibliography is arranged in alphabetical order by author, and each title is accompanied by an annotation, most of which include composite reviews and critical analyses of the work"--Provided by publisher.